Frequent items maintaining algorithms in network traffic analysis - DU A-ning; CHENG Xiao-ming (Tongxin xuebao)
Maintaining frequent items in infinite data stream was to produce a list of items with their frequencies exceeding a threshold over a stream of current length n.It was quite useful in network traffic analyzing.After studying the demand of network analyzing systems,a packet stream analyzing model and a definition of frequent items maintaining problem was provided.An improved frequent items maintaining algorithm,which kept the deficient synopsis in limited memory was proposed based on analysis of existing algorithms.Experiments reveal that improved algorithm fulfill the need of high-speed TCP/IP packet stream.